Análisis del uso del recurso educativo digital denominado ¨Juego y estimulo mi cerebro¨ como herramienta para promover el desarrollo de habilidades de pensamiento lógico matemático en los estudiantes de quinto grado de educación general básica de la Unidad Educativa Particular Santa Mariana de Jesús, de la ciudad de Loja, en el año lectivo 2022- 2023 - Gualan Zapata, Katherine Mishel (2023)
Technology use in the classroom reflects the reality of the environment in which students will be immersed in the future, so it is essential to integrate it effectively into the educational process so that they generate skills that allow them to respond to the problems of the XXI century. The present research had as its purpose to analyze the use of the digital educational resource called "I play and stimulate my brain" as a tool to promote the development of mathematical logical thinking skills in the fifth-grade students of general basic education of the Santa Mariana de Jesus Private Educational Unit, in Loja city, in the school year 2022- 2023. The methodology used had as its basis the deductive method, with a quantitative/qualitative approach, being of exploratory-descriptive scope and finally the design of non-experimental character in coherence with article 216 of the Academic Regulations of the National University of Loja. The research describes within its results the pedagogical and technological elements of the digital educational resource, which consists of objectives, skills, contents, multimedia elements and a friendly interface that combines actors, buttons and menus. The activities of the resource were included in the didactic unit planning in various contents of the fifth-grade mathematics curriculum to promote the development of mathematical logic skills. Moreover, it was determined that the teacher made use of the educational resource during the classes in different didactic moments: anticipation, construction and consolidation. Finally, it was determined that the use of the digital educational resource called ¨I play and stimulate my brain¨ does promote the development of mathematical logical thinking skills in the population of students investigated. Keywords: Digital educational resources, Mathematical logical thinking, Math, Skills development.